Longitudinal Associations between Sexting, Cyberbullying and Bullying: Cross-Lagged Panel Analysis - Van Ouytsel, Joris (J Adolesc, 2019)
INTRODUCTION: While adolescent sexting, or the sending of sexually explicit images, has been cross-sectionally associated with bullying and cyberbullying, there is a lack of longitudinal studies in this area. To address this gap in the literature, we examined the longitudinal link between sexting and 1) traditional, in-person, bullying victimization and 2) cyberbullying victimization. METHODS: We used data from a longitudinal study of ethnically diverse adolescents recruited from multiple public high schools in southeast Texas. Three waves of data were used (T2, T3 and T4). Cross-lagged panel analysis was performed in Mplus to analyze the data. RESULTS & CONCLUSIONS: Cross-lagged panel analyses identified autoregressive effects for all three variables, and cross-lagged effects for cyberbullying. Sexting was associated with subsequent cyberbullying victimization across all time points, and T3 cyberbullying victimization was associated with engagement in sexting one year later. Furthermore, T2 cyberbullying victimization indirectly associated with T4 sexting via T3 cyberbullying victimization. For traditional bullying, a cross-lagged effect was found between T3 sexting and T4 offline bullying victimization. Although T2 sexting did not directly link to subsequent traditional bullying victimization, a significant mediation effect was identified such that T3 sexting mediated the effects of T2 sexting on T4 traditional bullying victimization. Results show that sexting adolescents may be at risk for (cyber)bullying victimization and highlight the need to address both sexting and bullying in prevention and intervention efforts.